Evaluation of Physicochemical, Spectral and Thermal Properties of Energy of Consciousness Healing Treated Iron Sulphate - Mahendra Kumar Trivedi; Snehasis Jana (Journal of New Developments in Chemistry, 2021)
Iron sulphate is used in the treatment of iron deficiency anaemia and other chronic disorders such as heart and kidney diseases. This study has the objective to analyze the impact of The Trivedi Effect®-Energy of Consciousness Healing Treatment on the physicochemical, spectroscopic and thermal properties of iron sulphate using various analytical techniques. In this, the test compound, i.e., iron sulphate was divided into two parts; one as control (without Biofield Energy Treatment), and the other as Biofield Energy Treated, which received the Biofield Energy Treatment remotely by the renowned Healer, Mr. Mahendra Kumar Trivedi. The PXRD analysis of the Biofield Energy Treated sample showed significant alterations in the range of -39.49 to 301.40% in the relative intensities, and from -15.40 to 33.36% in the crystallite sizes, compared with the control sample. The average crystallite size of the treated sample was also increased by 4.98% as compared to the control sample. The particle sizes in the treated sample at d10, d50, d90 and D(4,3) values were significantly increased by 67.12%, 47.72%, 33.18% and 42.01%, respectively; whereas, the specific surface area was significantly reduced by 38.39%, compared with the control sample. The TGA thermograms showed three steps of thermal degradation in which, the weight loss of Biofield Energy Treated sample in the first and second step was reduced by 5.82% and 16.09%, respectively, while, it was increased by 6.78% in the third step, compared to the control sample. The total weight loss in the treated sample was also reduced by 2.76%, along with slight alteration in the maximum thermal decomposition temperature, compared with the control sample. The DSC analysis showed the decrease in the melting temperatures of the 1st, 2nd and 4th peaks by 8.24%, 19.29%, and 0.61%, respectively, while 4.57% increase in the 3rd peak of the treated sample, compared with the control sample. The latent heat of fusion (ΔH) corresponding to the 1st, 2nd, 3rd and 4th peaks of the treated sample also showed alterations by -92.29, -86.29, 60.92, and 6.37%, respectively, compared with the control sample. The Trivedi Effect®-Consciousness Energy Healing Treatment might produce a novel polymorphic form of iron sulphate having increased crystallite and particle size along with enhanced thermal stability. It may help in improving the quality, safety and stability during the process of handling, storage, and shipment of the iron sulphate with better therapeutic response against iron deficiency anaemia.
Keywords: Iron Sulphate